The Tokyo 2020 terminology of liver anatomy and resections: Updates of the Brisbane 2000 system. (20th December 2021) - Wakabayashi, Go; Cherqui, Daniel; Geller, David A.; Abu Hilal, Mohammed; Berardi, Giammauro; Ciria, Ruben; Abe, Yuta; Aoki, Takeshi; Asbun, Horacio J.; Chan, Albert C. Y.; Chanwat, Rawisak; Chen, Kuo‐Hsin; et al.
Abstract: Background: The Brisbane 2000 Terminology for Liver Anatomy and Resections, based on Couinaud's segments, did not address how to identify segmental borders and anatomic territories of less than one segment. Smaller anatomic resections including segmentectomies and subsegmentectomies, have not been well defined. The advent of minimally invasive liver resection has enhanced the possibilities of more precise resection due to a magnified view and reduced bleeding, and minimally invasive anatomic liver resection (MIALR) is becoming popular gradually. Therefore, there is a need for updating the Brisbane 2000 system, including anatomic segmentectomy or less. An online "Expert Consensus Meeting: Precision Anatomy for Minimally Invasive HBP Surgery (PAM‐HBP Surgery Consensus)" was hosted on February 23, 2021. Methods: The Steering Committee invited 34 international experts from around the world. The Expert Committee (EC) selected 12 questions and two future research topics in the terminology session. The EC created seven tentative definitions and five recommendations based on the experts' opinions and the literature review performed by the Research Committee. Two Delphi Rounds finalized those definitions and recommendations. Results: This paper presents seven definitions and five recommendations regarding anatomic segmentectomy or less. In addition, two future research topics are discussed. Conclusions: The PAM‐HBP Surgery Consensus has presented the Tokyo 2020 Terminology for Liver Anatomy and Resections. The terminology has added definitions of liver anatomy and resections that were not defined in the Brisbane 2000 system. Abstract : Highlight The Tokyo 2020 terminology has added definitions of liver anatomy and resections that were not defined in the Brisbane 2000 system. It shows how to identify segmental borders and anatomic territories of less than one segment. This figure shows that Sg 5 consists of three cone units.